PERBANDINGAN PENGUKURAN WAKTU BAKU DENGAN METODE STOPWATCH TIME STUDY DAN METODE READY WORK FACTOR (RWF) PADA DEPARTEMEN HAND INSERT PT. SHARP INDONESIA - Nataya Charoonsri Rizani; Dian Mardi Safitri; Prita Ayu Wulandari (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
Production target of Department Hand Inserts PT Sharp Indonesia which was often not achieved, making the company intended to know the cause of the problem. Time study was needed to set production targets against operator’s ability. Time study established by the holding company of Japan using ready work factors (RWF) method. To determine conformity RWF method, a comparison with stopwatch time study was conducted. There were differences in the value of standard time with both methods. The differences due to value of rating operator performance and allowance. The value in RWF method was smaller than the findings in the field. After a change of both value the difference between the two methods became smaller. After that with standard time from RWF method was calculated operator's ability to produce. The results indicated that the ability of the operator under the production target, so improvement was needed.